انحراف الشباب وطرق علاجة : دراسة في ولاية سلانجور - Arifa Suriati Awang (2009)
This research is a project for the partial fulfillment of the requirements for the Bachelor Degree of Syariah and Judiciary from The Islamic University College of Malaysia (KUIM), Session 2002 1 2003. It discusses "the Deviation of Behavior among teenagers in the state of Selangor and the Methods of Resolving it" through the analysis of the causes and factors of this deviation using the statistics available. 'I?le researcher, in order to achieve the objectives of this research, has adopted a methodology which combines between the library research, the inductive method, and the analytical method. It applied also the techniques of observation, interview and the analysis. The researcher has specified the legal rule for this issue and the ways which help in tackling it educationally and according to Islamic worldview. Finally, the researcher- based on the findings - calls for the continuation of research in this issue because of the spread of deviation of behavior among teenagers and its danger on Muslim teenagers.